2015
DOI: 10.1007/s12471-015-0666-9
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in quality of life predicts mortality in adult patients with pulmonary arterial hypertension due to congenital heart disease

Abstract: BackgroundDecrease in quality of life (QoL) in left-sided heart failure precedes poor survival, which can be reversed with exercise training. We investigated whether QoL is associated with mortality in pulmonary arterial hypertension due to congenital heart disease (PAH-CHD) patients.MethodsIn this observational study, PAH-CHD adults referred for PAH-specific therapy were included. QoL surveys (SF36) were recorded during 2 years of therapy. Based on shift in SF36 scores during this period, patients had either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Yet, health-related quality of life questionnaires provide valuable information on the burden of pulmonary arterial hypertension on the patient's day-to-day living and have also been associated with prognosis. 39,40 In our study, the generic SF-36 and pulmonary hypertensionspecific CAMPHOR questionnaires presented strong inter-domain correlations as observed previously in patients with pulmonary hypertension 41 and were strongly associated with therapeutic objectives as assessed by NYHA functional class and the 6-minute walk distance, supporting their use in clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“…Yet, health-related quality of life questionnaires provide valuable information on the burden of pulmonary arterial hypertension on the patient's day-to-day living and have also been associated with prognosis. 39,40 In our study, the generic SF-36 and pulmonary hypertensionspecific CAMPHOR questionnaires presented strong inter-domain correlations as observed previously in patients with pulmonary hypertension 41 and were strongly associated with therapeutic objectives as assessed by NYHA functional class and the 6-minute walk distance, supporting their use in clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“…Quantitative measurement of HRQOL is heavily dependent on patient reported questionnaires and in the field of PAH the use of the SF-36 questionnaire is limited to a few studies ( Chua et al, 2006 ; Taichman et al, 2005 ; Zlupko et al, 2008 ). More recently in a subgroup of patients PAH due to congenital heart disease it was found that a decrease in physical aspects of HRQOL may be a determinant of mortality ( Blok et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…[6]). Assessing quality of life can be beneficial in medical practice; allowing an individual to self-assess their health status has shown to be a strong indicator and predictor of mortality [7, 8]. Additionally, by assessing the subjective effect of living with a disease or disability it is possible to identify high risk groups at which to target health interventions, to improve quality of life and satisfaction of intervention protocols [9].…”
Section: Introductionmentioning
confidence: 99%